Description of the Larvae of Anastrepha curitis, Anastrepha pickeli and Anastrepha pulchra (Diptera: Tephritidae) - Dutra, Vivian Siqueira; Ronchi-Teles, Beatriz; Steck, Gary J.; Rodriguez, Erick J.; Norrbom, Allen L.; Sutton, Bruce D.; Silva, Janisete Gomes (Proceedings of the Entomological Society of Washington, 2018)
We describe and illustrate for the first time the third-instar larvae of three Anastrepha species, Anastrepha pickeli Lima, Anastrepha pulchra Stone, and Anastrepha curitis Stone, and also the second instar of A. curitis. Structures such as the cephalopharyngeal skeleton and spiracles are described using optical and scanning electron microscopy. We describe characteristics of the ventral surface of the mandible for the first time for fruit fly larvae. © 2018 Entomological Society of Washington. All Rights Reserved.